2019
DOI: 10.1177/2059513119830519
|View full text |Cite
|
Sign up to set email alerts
|

London calling Gaza: The role of international collaborations in the globalisation of postgraduate burn care education

Abstract: Burn injuries represent a significant epidemiological problem, with the vast majority occurring in low- to middle-income countries. These regions also represent areas where lack of socioeconomic growth and geopolitical instability pose additional barriers not only to healthcare provision but also to the acquisition of continuing professional development. Long-distance, web-based learning programmes (‘tele-education’) have been identified as a successful and powerful means of propagating up-to-date medical educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Participants described remote teaching as a proven measure used when teaching was disrupted, but consistent with recent literature the availability of internet, appropriate equipment, or access to platforms remained challenges (32)(33)(34).…”
Section: Discussionmentioning
confidence: 61%
“…Participants described remote teaching as a proven measure used when teaching was disrupted, but consistent with recent literature the availability of internet, appropriate equipment, or access to platforms remained challenges (32)(33)(34).…”
Section: Discussionmentioning
confidence: 61%
“…A meta-analysis of over one-thousand research articles on the topic by the U.S. Department of Education con rmed the e cacy of distance-learning (Means et al 2009). A number of organisations (including OxPal (Penfold & Ali 2014), MedicineAfrica (Bowen et al 2012) and Queen Mary University of London (Theodorakopoulou et al 2019)) have previously demonstrated this to be true in a medical education context in LMICs. An online health research course was shown to equally enhance health research capacity when compared to in-person instruction in a small RCT of Indian research scientists by Aggarwal et al (Aggarwal et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Given current insufficient numbers of educators among the healthcare workforce in north west Syria, more efforts to capitalise on available technologies which support the education of HCWs is needed. Tele-education has been used in other conflict and post-conflict settings including Iraq, Gaza [41,42], Bosnia and Herzegovina [43]; some of these have been collaborations with international universities e.g. Mayo clinic, Queen Mary University in London and have usually focused on a single topic e.g.…”
Section: Tele-education and Distance Learningmentioning
confidence: 99%
“…Though this has occurred in other conflict affected settings e.g. Gaza, Iraq, Balkans, the extent to which these organisations have responded to the needs in north west Syria and their sustained attempts to meet critical gaps and to replace previous educational institutions and accreditation bodies has been more extensive than seen in previous conflicts [41,42,48]. This may represent a shift change in the humanitarian system whereby HCW education (with regulation/ certification/ accreditation) is prioritised alongside other key sectoral needs, particularly for complex and protracted crises such as Syria.…”
Section: Towards a Shift In Prioritising Healthcare Worker Education mentioning
confidence: 99%